Outcomes Associated with 5-HT(3)-RA Therapy Selection in Patients with Chemotherapy-Induced Nausea and Vomiting: A Retrospective Claims Analysis - Faria, Claudio (Engage Healthcare Communications, LLC, 2014)
BACKGROUND: Chemotherapy-induced nausea and vomiting (CINV) is a common side effect of chemotherapy, and may present during the administration of chemotherapy (ie, acute CINV) or within 25 to 120 hours of chemotherapy (ie, delayed CINV). Preventing CINV with the initiation of chemotherapy is important, because the risk for CINV in future chemotherapy cycles increases if CINV occurs in the first or previous treatment cycle. Inadequately controlled CINV is associated with increased resource utilization and costs, particularly for patients receiving highly or moderately emetogenic chemotherapy. OBJECTIVE: To evaluate the clinical and economic impacts of delayed CINV events in patients who receive initial and maintenance therapy with the newer-generation 5-hydroxytryptamine(3) receptor antagonist (5-HT(3)-RA) palonosetron compared with patients who receive initial and maintenance therapy with an older 5-HT(3)-RA agent. METHODS: A retrospective database analysis was conducted using the OptumInsight database covering the years 2005–2011 (96% commercially insured members, 4% Medicaid members). Patients with cancer who received initial therapy with an emetogenic single-day chemotherapy regimen and a 5-HT(3)-RA agent (ie, dolasetron, granisetron, ondansetron, or palonosetron) were included in the analysis. The outcomes measured included the overall rates of delayed CINV for cycles 1 to 6, by 5-HT(3)-RA cohort. For cycles 2 to 6, calculations were based on patients who experienced CINV in the previous cycle, maintained the same 5-HT(3)-RA for all cycles, and had chemotherapy with a similar level of emetic potential. The economic outcomes (ie, cost and utilization) were also collected and calculated. RESULTS: A total of 26,974 patients were included in the analysis. The overall rate for delayed CINV at cycle 1 was 15.6%, and the lowest rate was for palonosetron at 15%. The patients who initiated palonosetron had lower CINV rates throughout all cycles. The regression analysis compared individual agents to palonosetron and demonstrated higher odds of CINV in the second cycle for the older agents (ondansetron: odds ratio [OR], 1.41; 95% confidence interval [CI], 1.14–1.74; P <.002; granisetron: OR, 1.70; 95% CI, 1.39–2.08; P <.001; dolasetron: OR, 1.65; 95% CI, 1.27–2.15; P = .002). This trend continued through cycle 6, and not all ORs were significant. Over 6 cycles, ondansetron cost an additional $126,775 compared with palonosetron; granisetron an additional $169,838 versus palonosetron; and dolasetron an additional $148,960. CONCLUSIONS: Current guidelines support the use of 5-HT(3)-RA agents for the prevention of CINV. As shown in this analysis, the selection of a specific 5-HT(3)-RA agent has a clinical and subsequent economic impact on patients with cancer experiencing delayed CINV. Specifically, patients receiving therapy with palonosetron had a lower incidence of delayed CINV and incurred lower overall costs.